Heterogeneous Catalytic Conversion of Sugars Into 2,5-Furandicarboxylic Acid - Deshan, Athukoralalage Don K.; Atanda, Luqman; Moghaddam, Lalehvash; Rackemann, Darryn W.; Beltramini, Jorge; Doherty, William O. S. (Frontiers in Chemistry, 2020)
Achieving the goal of living in a sustainable and greener society, will need the chemical industry to move away from petroleum-based refineries to bio-refineries. This aim can be achieved by using biomass as the feedstock to produce platform chemicals. A platform chemical, 2,5-furandicarboxylic acid (FDCA) has gained much attention in recent years because of its chemical attributes as it can be used to produce green polymers such polyethylene 2,5-furandicarboxylate (PEF) that is an alternative to polyethylene terephthalate (PET) produced from fossil fuel. Typically, 5-(hydroxymethyl)furfural (HMF), an intermediate product of the acid dehydration of sugars, can be used as a precursor for the production of FDCA, and this transformation reaction has been extensively studied using both homogeneous and heterogeneous catalysts in different reaction media such as basic, neutral and acidic media. In addition to the use of catalysts, conversion of HMF to FDCA occurs in the presence of oxidants such as air, O2, H2O2 and t-BuOOH. Among them, O2 has been the preferred oxidant due to its low cost and availability. However, due to the low stability of HMF and high processing cost to convert HMF to FDCA, researchers are studying the direct conversion of carbohydrates and biomass using both a single- and multi-phase approach for FDCA production. As there are issues arising from FDCA purification, much attention is now being paid to produce FDCA derivatives such as 2, 5-furandicarboxylic acid dimethyl ester (FDCDM) to circumvent these problems. Despite these technical barriers, what is pivotal to achieve in a cost-effective manner high yields of FDCA and derivatives, is the design of highly efficient, stable and selective multi-functional catalysts. In this review, we summarize in detail the advances in the reaction chemistry, catalysts and operating conditions for FDCA production from sugars and carbohydrates.